The Situation and Prospects of Hungarian Rural Development Preceding EU Accession - Fürj, Zoltán (Acta Agraria Debreceniensis, 2004)
Today’s Hungarian rural development is defined by the fact, that Hungary will be a member state of the European Union from May 1, 2003. Our accession means the end of a long period, and new rural development programs that are going to build on the basic of previously accepted EU standards and experience will highlight the immediate future. From the Hungarian rural development programs I especially dealt with the SAPARD, AVOP and NVT, which in my opinion had and will have the greatest influence on the improvement of the Hungarian county. The AVOP and NVT are still under development (or just submitted to the EU), but their role in the future will be particularly essential, because these programs are going the act as the first programs in Hungary as a member state and a lot will depend on them in the improvement of the rural development.